Readiness for Organizational Change of Employee in Merger Situation (study in a State-owned enterprise Bank) - Sembiring, Lala Septiyani; Sulastiana, Marina; Lestari, Anissa; Abidin, Zainal (CV. ITTC INDONESIA, 2024)
Readiness for organizational change plays an important role in the change process. It shapes behavior that supports organizational change and makes employees strive harder to implement change. This study uses a descriptive quantitative method to describe the level of readiness for organizational change of employees at a State-owned enterprise Bank undergoing a merger process. 480 respondents were involved in this study, obtained through the two-stage cluster sampling technique. The study results showed that most respondents were in the high readiness for organizational change category, namely 69%, in the medium category 30.06%, and in the low category 0.4%. While the highest dimension is in managerial support (mean = 5.54) and the lowest is in personal valance (mean = 4.72). In addition, it was found that there were differences in the level of readiness for organizational change in several demographic factors, such as actors, such as sex, age, work location, job level, and education.